Choice of breeds and husbandry practices influencing the safety of milk and milk products from smallholder dairy cattle farms around Nairobi, focusing on brucellosis - Ndongo, F.K. (University of Hohenheim, 2009)
Kenya, which has over 85% of the dairy cattle population in East Africa, dominates dairy production and marketing in the region. Today most of Kenya’s 3 million dairy cattle are kept by smallholders who are concentrated close to urban consumption centres. Therefore, the peri-urban dairy sector plays an important role in the livelihood of smallholders in Kenya. But the sector is facing many constraints among which, poor husbandry practices, poor hygiene, and poor milk handlings are recognised as the major technical challenges. These constraints may lead to high prevalence of livestock diseases such as brucellosis that contaminate milk and milk products and threaten the health of consumers. The objectives of the present study were to describe the husbandry practices applied by the smallholder dairy farmers in a peri-urban area in Kenya, determine the prevalence of brucellosis in the area and to test whether the prevalence of brucellosis is influenced by the breed kept and husbandry practices applied by the farmers. One hundred farms and 20 milk shops (retailers) were surveyed in Kasarani Division (around Nairobi) using a questionnaire with open and closed questions to collect data about husbandry practices and perception of the farmer on brucellosis. Unboiled milk samples were collected in each farm and the 20 shops surveyed and investigated for Brucella abortus and B. melitensis using Milk Ring Test (MRT) and indirect ELISA. Finally, a focus group discussion was conducted in order to collect other information about the availability of feed throughout the year, advantages and disadvantages of the different marketing channel, the issue of hygiene and their knowledge, practices and attitudes about bovine and human brucellosis. The discussion lasted for two and half hours. The study showed that 2 dairy systems prevail in the area; semi-zero grazing (14%) and zero grazing (86%). The main feedstuffs used were Pennisetum purpureum (Napier grass) which was the predominant feed (96%), followed by dairy meal (90%), crop residues (84%) and natural grass (77%). Brewery waste, hay and poultry waste were also used at a lower extend. Crossbreds are widely used in the area (53%), followed by pure exotic breeds (33%) and very few local breeds (8%). Friesian is the predominant breed found in the farms (79%) followed by Ayrshire (44%), Guernsey (14%) and local breeds (8%). The mating technique which prevails in the area is artificial insemination (86%). Cows were milked with hands in 99% of the farms and the milk marketing is dominated by the informal market in which 66% of farmers sell their milk directly to consumers, 26% of farmers sell milk to milk sellers and only 7% sell milk exclusively to cooperatives. The result from MRT revealed an apparent prevalence of 6.9% in zero grazing farms, 0% in semi-zero grazing farms, 7.5% in crossbreds, 5% in pure exotic breeds and 0% in local breeds. ELISA showed a prevalence of 0% irrespectively of the system and the breed. At market levels MRT and ELISA did not reveal any case of brucellosis. Nevertheless, the study noted some practices such as feeding with natural grasses (77%), grazing (14%), and the use of bull service for breeding (8%) which are likely to expose cattle to brucellosis. Despite the absence of brucellosis revealed by ELISA, 3% of farmer reported to have got a case of brucellosis in the family. Only 24% of farmers were aware of the existence of brucellosis as a potential disease while of these, only 8% had knowledge of brucellosis transmission. Risks for man to contract brucellosis was very low considering the fact that milk was boiled prior to consumption in all households and shops visited. However, 2% and 100% of dairy farmers and milk sellers respectively made fermented milk without boiling milk; this practice may predispose people to brucellosis. In addition, 10% of farmers still handle aborted foetus with bare hands and are therefore exposed to brucellosis. The proportion of dairy farmers who had knowledge that cattle can transmit brucellosis to man was very low (8%). At market level, only one seller knew that brucellosis can be transmitted to man through milk. Education of dairy farmers and milk sellers on the transmission pathways and risk of brucellosis is required in order to keep the prevalence of brucellosis low in Kasarani division.